Participação de crianças e adolescentes com desenvolvimento normal, paralisia cerebral e Síndrome de Down no contexto domiciliar - Maíra Ferreira do Amaral (2012)
Introduction: The regular participation of children and adolescents in home context contributes to the development of a variety of behaviors and skills required to an independent life. Children with cerebral palsy and Down syndrome show limitations to the participation in contexts such as school and community. However, it’s remarkable that there’s a shortage of studies on the children participation specifically in home context. Objectives: To compare participation in home context between children and adolescents with normal development (ND), with cerebral palsy (PC) and with Down Syndrome (SD). Methods: Observational transversal study in which participated 75 children and adolescents from 6 to 14 years old, with 25 in each group (DN, PC, SD). To evaluate the participation in home context, the Children Helping Out: Responsibilities, Expectations and Supports was used. Multiple linear regression models were used to test the predictive value of children and family structure related variables. Results: Children and adolescents with SD presented major limitations to participation, when compared to participants with PC and DN. DN children and adolescents presented more independence to home tasks, when compared to PC and SD children. Age and Intellectual Quotient are predictive factors to participation, nevertheless slightly explicative. Conclusions: Results imply that mental illness, rather than motor impairment, imposes restrictions to participation in home context and to autonomy towards involvement in home tasks. It is possible that family values and beliefs are related to participation in home context, though further studies with those variables are necessary.